Teknik pelukisan tokoh utama dalam novel Alaska karya Nisa Fatma - Amelia, Fara; Israhayu, Eko Sri (Jurnal Pendidik Indonesia, 2025)
This study aims to describe the characterization techniques of the main characters and to identify the most dominant technique used in the novel Alaska by Nisa Fatma. There are two types of characterization techniques: direct and indirect. The research employs a qualitative descriptive method with a structuralist approach, using Nurgiyantoro's theory as the foundation for analyzing characterization techniques. Data were collected using reading and note-taking techniques. The results show that in Alaska, written by Nisa Fatma, there are two main characters: Alaska Tahta Wardana and Alana Juwanda. Nisa Fatma predominantly uses behavioral description as the main technique in portraying her characters. The analysis of characterization techniques in this novel is important to understand how the author builds strong and engaging characters. This research is expected to contribute to studies on main character portrayals in novels and broaden the understanding of how authors develop characters in ways that align with their perspectives and effectively evoke readers' empathy.